2008
DOI: 10.1073/pnas.0805255105
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and measurement of an isotopically distinct source of sulfate in Earth's atmosphere

Abstract: maritime vessels ͉ triple oxygen isotope ͉ aerosols ͉ polluted marine boundary layer ͉ sea salt spray

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 29 publications
2
62
0
Order By: Relevance
“…Primary sulfate [i.e., S(VI) produced at the emission source] exhibits a higher enrichment in δ 18 O = 20-45‰ and Δ 17 O = 0 (50-52). Secondary sulfate is formed when SO 2 is oxidized in the atmosphere via homogeneous and heterogeneous pathways (51). The δ 18 O of secondary sulfate thus represents a juxtaposition of the highly variable water isotopic signature derived during SO 2 oxidation processes at varying latitudes and altitudes (10,53,54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary sulfate [i.e., S(VI) produced at the emission source] exhibits a higher enrichment in δ 18 O = 20-45‰ and Δ 17 O = 0 (50-52). Secondary sulfate is formed when SO 2 is oxidized in the atmosphere via homogeneous and heterogeneous pathways (51). The δ 18 O of secondary sulfate thus represents a juxtaposition of the highly variable water isotopic signature derived during SO 2 oxidation processes at varying latitudes and altitudes (10,53,54).…”
Section: Discussionmentioning
confidence: 99%
“…2 requires the presence of a specific source, but it must be of higher δ 18 O and low Δ 17 O. Laboratory experiments, field observations, and numeric simulation of sulfur oxidation (14,28,50,51) have shown that the δ 18 O of sulfate coupled with Δ 17 O can be used to distinguish between primary and secondary sulfates. Primary sulfate [i.e., S(VI) produced at the emission source] exhibits a higher enrichment in δ 18 O = 20-45‰ and Δ 17 O = 0 (50-52).…”
Section: Discussionmentioning
confidence: 99%
“…Note that SO 2 emission in east China also kept increasing from 1985 to (Streets et al, 2000Lu et al, 2010), suggesting that the visibility degradation in southeast China may in part be due to transport of secondary sulphate formed upwind (i.e., over the east China coast). Measurements of the mass-independent fractionated oxygen isotopes in sulphate allow the primary and secondary sulphate contributions to be identified, and the oxidation pathways of secondary sulphate to be quantified Alexander et al, 2005;Patris et al, 2007;Dominguez et al, 2008). Such measurements can bring us closer to identifying the dominant oxidation mechanisms in the future.…”
Section: Relationship Between Visibility and Air Pollutantsmentioning
confidence: 99%
“…Oxygen triple-isotope ( 16 O, 17 O, 18 O) measurements of sulfate have been used previously to infer the atmospheric formation pathways of sulfate in the present Alexander et al, 2005Alexander et al, , 2009Patris et al, 2007;Dominguez et al, 2008) and paleo- (Alexander et al, 2002(Alexander et al, , 2003(Alexander et al, , 2004Kunasek et al, 2010) atmosphere. Most chemical and physical processes fractionate isotopes in a mass-dependent manner.…”
Section: E D Sofen Et Al: Preindustrial Oxidants and Isotopes Of Imentioning
confidence: 99%